2011
DOI: 10.1186/1472-6920-11-55
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional evaluation of a longitudinal consultation skills course at a new UK medical school

Abstract: BackgroundGood communication is a crucial element of good clinical care, and it is important to provide appropriate consultation skills teaching in undergraduate medical training to ensure that doctors have the necessary skills to communicate effectively with patients and other key stakeholders. This article aims to provide research evidence of the acceptability of a longitudinal consultation skills strand in an undergraduate medical course, as assessed by a cross-sectional evaluation of students' perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
0
13
0
4
Order By: Relevance
“…Many satisfaction surveys have showed that learners prefer this method of training over traditional programs. 25,26 Moreover, outcome studies reveal that students trained in longitudinal models perform at least as well as their traditionally trained peers. From the Harvard program, students completing a longitudinal course performed at least as well as peers in traditional clerkships on the National Board of Medical Examiners subject exams and objective structured clinical exams and scored higher on year-end clinical skills self-assessment exams.…”
Section: Research Questionmentioning
confidence: 99%
“…Many satisfaction surveys have showed that learners prefer this method of training over traditional programs. 25,26 Moreover, outcome studies reveal that students trained in longitudinal models perform at least as well as their traditionally trained peers. From the Harvard program, students completing a longitudinal course performed at least as well as peers in traditional clerkships on the National Board of Medical Examiners subject exams and objective structured clinical exams and scored higher on year-end clinical skills self-assessment exams.…”
Section: Research Questionmentioning
confidence: 99%
“…The other studies (Papageorgiou et al 16 ; Redwood et al 22 ; Huntoon et al 20 ; Brehm et al 12 ; Zink, Halaas and Brooks 4 ) used assessments of professionalism associated with practical experiences and the application of health teaching strategies, thereby demonstrating a dimension of doing/simulating. These studies reached the "Shows" and "Does" levels of the pyramid represented in Figure 2 of the present study, revealing a dimension of the research in the practical field.…”
Section: Comunicação Saúde Educação 2016; 20(58):679-90mentioning
confidence: 99%
“…It is known that professionalism should be assessed longitudinally and combine different approaches to collect the personal, interpersonal, institutional and social characteristics of the individual assessed, which is an international challenge15. Faced with this question, it stands yet the importance of qualitative evaluation of the attributes of professionalism, in view the concept of complexity and its practical application 4,16 .…”
Section: Comunicação Saúde Educação 2016; 20(58):679-90mentioning
confidence: 99%
See 2 more Smart Citations